An audit of trauma deaths occurring in the accident and emergency department. Issue 2 (June 1989) - Gordon, M W; Luke, C; Robertson, C E; Busuttil, A
Abstract : A retrospective study of all patients who died following trauma in the Accident and Emergency Department of the royal Infirmary of Edinburgh over a 4-year period revealed 50 patients (0.0002% of total attendances). Injury severity scores (ISS) and probabilities of survival (Ps) were calculated for all patients. Two-thirds had a Ps of zero while 7 (14%) had a Ps of 0.5 or more. From the information in the case records and at autopsy four deaths (8%) were considered to have been potentially avoidable on the basis of inadequate or inappropriate management. There were a further eight cases (16%) whose management appeared to have been unsatisfactory but who would have been expected to die even if given optimal treatment. These cases are discussed in detail. Difficulty in diagnosing thoracic injuries and delay in giving appropriate treatment were by far the commonest errors encountered. A protocol for the treatment of patients in cardiorespiratory arrest with thoracic injuries is presented. The importance of regular audit of trauma cases and deaths is emphasized.